2002
DOI: 10.1108/01435120210432273
|View full text |Cite
|
Sign up to set email alerts
|

Marketing information services in Botswana: an exploratory study of selected information providing institutions in Gaborone

Abstract: A study of selected information providing institutions, in particular special libraries, in Gaborone, Botswana, reveals that a majority are in favour of marketing their services to their users. In practice, very few libraries undertake formal marketing planning and prepare marketing plans. Marketing was therefore unplanned. Promotion is the most commonly used element of the marketing mix. However, library marketing can no longer be confined to this one element. The whole range of marketing activities is needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Kanaujia (2004) further identified a lack of knowledge and a misconception about the concept of marketing on the part of librarians as major barriers. In Botswana, Nkanga (2002) found that the major challenges according to the respondents in that study were shortage of staff (19 per cent), financial constraints (15 per cent) and a lack of training in marketing. In the case of Nigeria, another study identified the non-responsive attitude of staff towards marketing as being a major factor.…”
Section: General Marketing Tools and Strategiesmentioning
confidence: 85%
“…Kanaujia (2004) further identified a lack of knowledge and a misconception about the concept of marketing on the part of librarians as major barriers. In Botswana, Nkanga (2002) found that the major challenges according to the respondents in that study were shortage of staff (19 per cent), financial constraints (15 per cent) and a lack of training in marketing. In the case of Nigeria, another study identified the non-responsive attitude of staff towards marketing as being a major factor.…”
Section: General Marketing Tools and Strategiesmentioning
confidence: 85%
“…A variety of techniques have been used to market library services and resources. Nkanga (2002) noted that marketing channels such as personal contacts, circulars, memos, telephone calls, meetings, direct mailing, displays, talks, newsletters, library tours, and leaflets were widely used. So also, Zhixian (2016) noted the channels of marketing library services, such as one-to-one conversations, classroom instruction, training sessions, faceto-face events and workshops, and digital media such as the library website and social media that were perceived to be most effectively used to promote services and resources.…”
Section: Various Channels and Strategies University Academic Librarie...mentioning
confidence: 99%
“…Perhaps it is as a result of this that libraries have been seen to be behind comparable organisations in their approach to marketing (Doherty, Saker, & Smith, 1998). Another reason that has often been offered is that librarians have a negative attitude towards marketing, although, recent research has shown that this is not the case; librarians are overall positive about marketing (Aharony, 2009;Nkanga, 2002). Staff at all levels of a library can impact on how successfully marketing is executed, meaning that any difference in attitude or opinion between strategic and operational staff will influence the implementation of marketing strategies (Harrison & Shaw, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%